Quantification and qualification of complication risks at use of non-steroid anti-inflammatory drugs as a basis for recommendations on their use and prophylaxis - Andrey Evgenyevich Karateev (Современная ревматология)
Non-steroid anti-inflammatory drugs (NSAID) were and still remain the main means for arresting acute and controlling chronic pains in therapeutic practice. However, serious complications that may be caused by these drugs essentially limit their application. Therapists need distinct and reasonable guidelines on NSAID prescription depending on presence of a comorbid pathology and risk factors associated with the gastrointestinal tract and cardiovascular system. World renowned experts have been actively studying this problem. The main aspects of NSAID efficiency and safety are discussed in this study; the risk factors are ranked according to their significance; and an algorithm of reasonable drug prescription, including prevention of potential complications, is proposed.